How supranational institutions benefit from crises: Member states' solidarity and the EU's image during the COVID-19 pandemic - Papageorgiou Achillefs; Immonen Waltteri (SAGE PUBLICATIONS LTD, 2023)
In this article, we demonstrate how solidarity between member states can have a positive effect on the image of the EU, even if the latter's actions in handling a crisis such as the COVID-19 pandemic are deemed unsatisfactory. Employing data from a special Eurobarometer survey enriched with data from the Oxford's COVID-19 government response tracker, we show that European citizens who are more satisfied with interstate solidarity have to a greater extent a positive image of the EU compared to citizens who are less satisfied. We also show that this effect is further pronounced in the case of EU citizens who are less satisfied with institutional solidarity, which is the solidarity going from EU institutions to the member states.